2006
DOI: 10.1038/sj.npp.1301031
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Serotonin Transporter Protein after MDMA and Other Ring-Substituted Amphetamines

Abstract: We studied in vivo expression of the serotonin transporter (SERT) protein after 3,4-methylenedioxymethamphetamine (MDMA), p-chloroamphetamine (PCA), or fenfluramine (FEN) treatments, and compared the effects of substituted amphetamines to those of 5,7-dihydroxytryptamine (5,7-DHT), an established serotonin (5-HT) neurotoxin. All drug treatments produced lasting reductions in 5-HT, 5-HIAA, and [ 3 H]paroxetine binding, but no significant change in the density of a 70 kDa band initially thought to correspond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
91
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 56 publications
(74 reference statements)
3
91
1
Order By: Relevance
“…Wang et al (2004b) have reported that SERT expression remains unchanged two weeks after a multiple-dose regimen of MDMA despite studies that have decreased radioligand binding to SERT. However, these results are contradicted by a recent report of Xie et al (Xie et al, 2006) in which a MDMA-induced reduction in SERT protein expression was demonstrated, suggesting a loss of 5-HT axons. Additionally, studies have indicated a lack of Fluoro-Jade-B positive neurons in the hippocampus and striatum following administration of MDMA, although a limited number of degenerating neurons have been noted in other brain regions (Schmued, 2003).…”
contrasting
confidence: 55%
“…Wang et al (2004b) have reported that SERT expression remains unchanged two weeks after a multiple-dose regimen of MDMA despite studies that have decreased radioligand binding to SERT. However, these results are contradicted by a recent report of Xie et al (Xie et al, 2006) in which a MDMA-induced reduction in SERT protein expression was demonstrated, suggesting a loss of 5-HT axons. Additionally, studies have indicated a lack of Fluoro-Jade-B positive neurons in the hippocampus and striatum following administration of MDMA, although a limited number of degenerating neurons have been noted in other brain regions (Schmued, 2003).…”
contrasting
confidence: 55%
“…Chronic antidepressant treatments can also result in decreased SERT binding, but this reduction is thought to reflect a downregulation of SERT expression (Benmansour Hirano et al, 2005). It is important to acknowledge that debate continues in the literature regarding the interpretation of MDMA-induced changes in SERT (measured by radioligand binding vs immunoblotting (see Wang et al, 2004Wang et al, , 2005Xie et al, 2006)) as well as other putative measures of serotonergic neurotoxicity such as reduced levels of 5-HT and 5-HIAA (O'Callaghan and Miller, 1993). In the present study, the significant difference in SERT binding between the CITAL/SAL and the SAL/SAL animals complicates interpretation of the 10-week neurochemical data.…”
Section: Discussionmentioning
confidence: 99%
“…MDMA reduces brain levels of serotonin (5-HT), the 5-HT metabolite 5-HIAA, and 5-HT transporter (SERT) binding (reviewed in Green et al, 2003). Immunohistochemical studies using antibodies against 5-HT or SERT have also found decreased immunoreactive fiber density in several forebrain areas of animals treated with MDMA (O'Hearn et al, 1988;Wilson et al, 1993;Xie et al, 2006). Taken together, these findings have generally been interpreted to reflect a pruning of serotonergic fibers (sometimes referred to as a distal axotomy) in the affected areas (Green et al, 2003; although also see Wang et al, 2004Wang et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus, striatum, and cortex have intermediate SERT densities (28,29). In the biodistribution studies, the highest ratio of the brain region of interest to the cerebellum was the hypothalamus-to-cerebellum ratio, suggesting that the lig- ands correctly targeted SERT in vivo.…”
Section: Discussionmentioning
confidence: 99%